Exchange Rate Liberalization in Selected Sub-Saharan African Countries Successes, Failures, and Lessons - Maehle, Nils (IMF Working Papers; Working Paper ;, 2013)
Many sub-Saharan African (SSA) countries liberalized their economies in the 1980s and early 1990s. This paper reviews the foreign exchange regime reforms in selected SSA, and their associated macroeconomic policies and economic performance during and after these reforms were undertaken. Before liberalization, most of the reviewed countries were characterized by extensive foreign exchange rationing, sizeable black market premiums, and declining per capita real income. Today, the countries that successfully reformed look markedly different. Rationing and parallel market spreads are a distant memory, and per capita income has increased sharply.